Investigating the Effectiveness of Tiger-Nut Oil (Cyperus esculentus L.) as Base Fluid in Synthetic-Based Mud - Ehwarieme, Favour; Akintola, Sarah A. (European Journal of Applied Sciences, 2023)
Due to the environmental effects and following the stringent regulations on drilling operations and the associated drilled cutting disposal, drilling fluid with less environmental impact are highly desirable over the conventional diesel based mud. This study seeks to determine the effect of ester derived from the oil of tiger nut using alkali catalyzed transesterification as base fluid for the formulation of a synthetic base mud. A total of four mud samples were formulated, three samples of 10ppg synthetic based muds were formulated using the ester at 70:30, 75:25, and 80:20 Oil-water ratio. The last mud sample was formulated using diesel as base fluid but at 75:25 Oil-water ratio. The fresh oil and its ester were characterized. The tiger nut ester was purified and the compositional analysis of the ester was carried out using the Fourier transform infrared spectrometry. The API recommended procedure was used to determine the mud samples density, rheological, filtration and emulsion properties. The result of the FTIR shows an absorption band at 1743.56 cm-1 indicates the presence of C=O of an ester. The result of the density of the fresh Tiger Nut Oil (TNO) and the ester are 0.98 and 0.87respectively, the viscosities are 25.7cp and 3.25cp respectively, the flash point and pour point are 173oC and -25oC, and 160oC and -15oC respectively. The plastic viscosity and yield point of the synthetic based mud ranges between 7.0cp to 16.0cp and 9.0lb/100sqft to 46.0lb/100sqft, while 9.0cp to 14.0cp and 20lb/100sqft to 27lb/l00sqft was measured for diesel oil-based mud. The filtrate volume and mud cake thickness for the synthetic based mud at 70:30, 75:25, and 80:20 oil-water ratio are 2.6ml and 1.2mm, 3.8ml and 1.1mm, 4.1ml and 1,0mm respectively, while 15.6 and 5mm were recorded for diesel oil based mud. The gel strength at 10sec and 10min of the synthetic based mud ranges between 6.0 and 11.0, while 7.0 and 8.0 were recorded for the oil based mud. These result shows that the ester based synthetic oil compared favorably with diesel in the formulation of drilling mud. From the result, it is observed that esterified TNO can as a base fluid for a synthetic base mud, but further research on the most cost effective way of producing the oil from tiger nut.